Investigaciones actuales en el curtido de pieles de animales mayores de abasto - Peña Mauricio, Carlos Martín (2017)
The objective of the present work was to know the most recent investigations on the tanning of skins of older animals of supply; by collecting information on research related to the topic, since many of them are specific and deal with a portion or a particular benefit, so that it can serve as a basis for future research. In animal skin tanning products, there are various and current investigations both in its process and preparation until the finished product of quality and with special characteristics necessary for its commercialization, these current processes have been achieved with different chemical and natural reagents as are: Tanned with chromium, tanning with alum, tanned to sulfur, combined tanning, mineral tanning, vegetable tanning, among others, these advances help to obtain a better product with a better durability thereof for consumer satisfaction. But it is the vegetable tanning with the help of a natural substance called tannin, the process that is most used today as the leather obtained has better characteristics, greater durability and less pollution by the process form of this industry. Also described in this thesis report are the production, the links of the value chains and the commercialization of the leather of larger animals of supplies